2012
DOI: 10.1136/ejhpharm-2012-000085
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour analysis of patients who purchase medicines on the internet: can hospital pharmacists facilitate online medication safety?

Abstract: Background Although there are numerous legal and regulated online pharmacies available on the internet, an abundance of illegitimate online pharmacies are offering medications without prescriptions and deliver products with unknown origins worldwide. Despite the fact that the problem has gained the attention of regulatory and health organisations, the awareness of patients and many healthcare professionals is relatively low. Objectives The purpose of this work is to assess the current situation of ordering me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 16 publications
1
38
0
Order By: Relevance
“…Online pharmacies can be beneficial to consumers (eg, convenience, privacy, free access to information, comparison shopping, etc) but can also carry with them numerous disadvantages (eg, lack of meaningful interaction with physician and pharmacists, misdiagnosis, inappropriate use of medicines, personal data protection, etc) [5-7]. These disadvantages and dangers are further exacerbated in the case of unlicensed and illegally operated online pharmacies.…”
Section: Introductionmentioning
confidence: 99%
“…Online pharmacies can be beneficial to consumers (eg, convenience, privacy, free access to information, comparison shopping, etc) but can also carry with them numerous disadvantages (eg, lack of meaningful interaction with physician and pharmacists, misdiagnosis, inappropriate use of medicines, personal data protection, etc) [5-7]. These disadvantages and dangers are further exacerbated in the case of unlicensed and illegally operated online pharmacies.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, online acquisition of contraceptives was made by female subjects properly covered by health insurance schemes (Kaskowitz et al, ). Overall, higher levels of education (Chiauzzi et al, ) were here associated with online search of health‐related information (Menon et al, ; Pew/Internet, ; CASA, ; Gordon et al, ; Kaskowitz et al, ; Atkinson et al, ; Pew/Internet, ; Kishimoto et al, ; Rajamma and Pelton, ; Wiedmann et al, ; Holtgräfe and Zentes, ; Mazer et al, ; Svorc, ; Fittler et al, ). Conversely, low literacy levels' subjects were more prone to make a purchase from “rogue Internet pharmacies” (Ivanitskaya et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…A Hungarian language questionnaire was developed by the authors (FA, VRGy pharmacists and KM psychologist) for this study based on previous research [57] and a preceding pilot study. In the online pilot study open questions were used, covering the topics of the study questionnaire to map the general attitudes of the prospective sample.…”
Section: Methodsmentioning
confidence: 99%
“…A Hungarian survey among hospital patients has showed that 8.4% of the respondents ordered drugs or dietary supplements online and 3.7% of the respondents are considering this option in the future. Gender, age and educational profile did not significantly affected the experience in ordering health related products from the Internet [57]. An Italian study in involving more than 100 adult subjects investigated the use of the Internet for searching for information on medicines, dietary supplements and disease.…”
Section: Consumers Purchasing Medicines Onlinementioning
confidence: 99%